Nurses perceptions of barriers to implementing family‐centered care in a pediatric setting: A qualitative study. Issue 2 (15th February 2017) - Boztepe, Handan; Kerimoğlu Yıldız, Gizem
Abstract: Purpose: This was a qualitative study conducted to explore the views of nurses regarding the practice of family‐centered care (FCC). Design and Methods: Eighteen nurses working in different units of a children's hospital in Turkey were included in the study. In‐depth interviews were conducted with the nurses to obtain detailed information about their perspectives on FCC activities. Results: Two main themes emerged from the data, each with subthemes. The first theme pertained to the nurses' opinions on FCC, and the second theme included their views on parents' participation during nursing rounds. Practice Implications: This study indicated that nurses had positive views of FCC activities and that they recognized the need for the family's continuing presence in the child's life, which were important findings. However, they stated that families' cultural characteristics were an obstacle. Therefore, to better implement this model, nurses should not only understand the model conceptually but also understand the rights, roles, and responsibilities of parents. To practice FCC appropriately, nurses need to have sufficient resources, appropriate education, and support from their managers.